Quality of life associated with breathlessness in the multinational Burden of Obstructive Lung Disease (BOLD) study: a cross-sectional analysis - Müller, Alexander (2025)
Introduction: Evidence of an association between breathlessness and quality of life from population-based studies is limited. We aimed to investigate the association of physical and mental quality of life with breathlessness across several low-, middle- and high-income countries. Methods: We analyzed data from 19,714 adults (31 sites, 25 countries) from the Burden of Obstructive Lung Disease (BOLD) study. We measured both mental and physical quality of life components using the SF-12 questionnaire and defined breathlessness as grade ≥2 on the modified Medical Research Council scale. We used multivariable linear regression to assess the association of each quality-of-life component with breathlessness. We pooled site-specific estimates using random-effects meta-analysis. Results: Both physical and mental component scores were lower in participants with breathlessness compared to those without. This association was stronger for the physical component (coefficient = -7.59; 95%CI -8.60, -6.58; I2 = 78.5%) than for the mental component (coefficient = -3.50; 95%CI -4.36, -2.63; I2 = 71.4%). The association between physical components and breathlessness was stronger in high-income countries (coefficient = -8.82; 95%CI -10.15, -7.50). Heterogeneity across sites was partly explained by sex and tobacco smoking. Conclusion: Quality of life is worse in people with breathlessness, but this association varies widely across the world.